Blockchain applications for peer-to-peer energy trading - Yang, Jiawei (Nanyang Technological University, 2023)
Peer-to-peer (P2P) energy trading is emerging as an increasingly popular approach because prosumers are allowed to trade their energy directly without intermediaries. This decentralised trading structure could be matched with the blockchain function to provide a more robust cyber-physical system as the blockchain is able to ensure the integrity of the transaction data and the privacy of prosumers. Since the consensus protocol of the blockchain determines its usage, a proper blockchain type and an effective pricing scheme design are required to safeguard the energy trading and improve the social welfare of the microgrid. In addition, a stable power delivery system is significant as it supports the energy trading. Therefore, the control system of the microgrid should also be safeguarded against any cyber attacks such as false data injection (FDI). The cryptographic mechanism and distributed ledger recording function enable the blockchain to provide a comprehensive protection for both P2P energy trading and control system. With the support of the smart contracts, designing a proper pricing scheme for energy trading and ensuring the security of the distributed secondary control for the frequency of the microgrid is a challenging task.